The relationship between rhinovirus infection and acute wheezing in young children with recurrent wheezing. (January 2019) - Zhu, Wen-Jing; Liu, Chuan-He; Zhao, Lin-Qing; Zhao, Min; Sha, Li; Chang, Li; Hao, Chun-Sheng; Qian, Yuan; Chen, Yu-Zhi
Asthma is a common chronic respiratory disease in childhood. The present study aims to assess the association between rhinovirus (RV) infection and acute wheezing in the occurrence of recurrent wheezing in 5-year old and younger children. A total of 109 children with recurrent wheezing and 70 children without wheezing (controls) were recruited from October 2013 to March 2015. Nasopharyngeal aspirate samples were obtained from all children. RV, human metapneumovirus (hMPV), and bocavirus (BoV) were tested by reverse transcription-polymerase chain reaction.Respiratory syncytial virus (RSV), parainfluenza virus (PIV), influenza virus (IV), and adenoviruses (ADV) were confirmed by detection of viral antigens via fluoroimmunoassay. Viral infection was more commonly detected in children with recurrent wheezing than in controls (odds ratio (OR): 6.10; 95% confidence interval (CI): 2.89–12.87). RV and RSV were found in both wheezing children and controls. However, RV was detected more in wheezing children than in controls (OR: 3.07; 95% CI: 1.37–6.90), followed by RSV (OR: 5.33; 95% CI: 1.53–18.62). Furthermore, RV more tended to infect wheezing children after infancy. Compared with children infected with other viruses, higher levels of eosinophil were found in wheezing children with RV infection ( P  < 0.05). RV was the main pathogen that induced exacerbation in young children with recurrent wheezing. Furthermore, the rate of RV infection was higher in children above 1 year old. RV infection might be associated with high levels of eosinophil.